The Story of America : Essays on Origins (Book collections on Project MUSE., 2012)
In The Story of America, Harvard historian and New Yorker staff writer Jill Lepore investigates American origin stories--from John Smith's account of the founding of Jamestown in 1607 to Barack Obama's 2009 inaugural address--to show how American democracy is bound up with the history of print. Over the centuries, Americans have read and written their way into a political culture of ink and type. Part civics primer, part cultural history, The Story of America excavates the origins of everything from the paper ballot and the Constitution to the I.O.U. and the dicti.